Effect of some inhibitors on kanamycin formation by Streptomyces kanamyceticus - Basak, K; Majumdar, S K (Folia microbiologica, 1976)
The formation of kanamycin is markedly inhibited by mercuric chloride, sodium iodoacetate, 2,4-dinitrophenol, sodium arsenite and sodium azide particularly when these are added at the start of fermentation. Less inhibition of kanamycin synthesis is observed in case of sodium 5,5-diethylbarbiturate, malonic acid, sodium arsenate and sodium fluoride. Inhibition of kanamycin synthesis is associated with growth inhibition in case of 2,4-dinitrophenol, sodium arsenite and sodium azide. Bacitracin and D-cycloserine have a stimulatory effect on kanamycin synthesis with slight inhibition of cellular growth. This stimulation might be due to accumulation of cell wallintermediates--aminosugar and sugar--which are shunted to the pathway of kanamycin synthesis. Penicillin lowers kanamycin synthesis by 65 percent as compared with 19 percent reduction of cellular growth. Chloramphenicol has a stimulatory effect at lower concentration (20 mug/ml), when it is added at 24 h of fermentation. At higher concentration (50 mug/ml) chloramphenicol shows marked inhibition of both cellular growth and antibiotic biosynthesis.
Keywords: azidy; arsen; chloramfenikol; chemická deprese; malonáty; jodacetáty; Streptomyces; Depression, Chemical; Azides; rtuť; Arsenic; Chloramphenicol; Mercury; Barbiturates; Bacitracin; fluoridy; Dinitrophenols; dinitrofenoly; barbituráty; buněčná stěna; Kanamycin; Cell Wall; Cycloserine; Fluorides; Malonates; bacitracin; Iodoacetates; cykloserin; kanamycin